4-H Volunteer Training Series: Recognizing Young People: 4H370, rev. 5/2024 - Bender, Georgene; Sachs, Geralyn; Hensley, Sarah; Toelle, Andrew; Cook, Kelsey; Ward, Marnie; Reighter, Shayla; Meringolo, Dallas; Quirie, Courtney (EDIS, 2024)
Developing a sense of belonging is one of the Essential Elements of a positive youth development experience. Creating an inclusive environment in your 4-H club programs and activities can help you achieve this goal. Providing many forms of recognition for all, not just for those who excel in competition with other youth, supports this sense of belonging.